Implementasi Nilai-nilai Multikulturalisme dalam Pembelajaran Pendidikan Agama Islam di SMAN 1 Kota Batu - Haj, Habil Syahril; Rossidy, Imron (ISLAMIKA, 2024)
This research explores the application of multiculturalism values in the teaching of Islamic Religious Education at SMAN 1 Kota Batu. Considering that Indonesia is a country with diverse ethnicities, nations, and religions, an inclusive educational strategy is needed to enhance tolerance and respect for differences. This research's primary focus is on the planning and implementation of multiculturalism values in the teaching of Islamic Religious Education. With a case study methodology, this research employs a qualitative approach. Observation, interviews, and documentation were used to gather data. The findings of the study indicate that the planning aligns with the profile of Pancasila student reinforcement and the application of a contextual approach, teaching that includes cultural diversity, collaborative activities, and character education, thereby providing a positive effect on multiculturalism values in the teaching of Islamic Religious Education.